Knowledge of Acute Stroke Management Among Healthcare Professionals: Development and Validation of Acute Stroke Management Questionnaire (ASMaQ) - Sim, Chun yang; Wan Asyraf, Wan Zaidi; Shamsul, Azhar Shah; Wan Nur Nafisah, Wan Yahya; Tan, Hui jan (Elsevier, 2021)
Background: Around 15.0% of all strokes occurred in hospitalised patients and studies showed significant delay in the stroke recognition and lack of awareness on thrombolytic therapy for acute ischaemic stroke (AIS) which lead to higher mortality for in-hospital stroke. We aimed to develop and validate a new instrument known as acute stroke management questionnaire (ASMaQ) to evaluate the awareness of healthcare professionals in managing acute ischaemic stroke cases. Methods: This study consisted of 3 steps; the formulation of ASMaQ draft, content validation and construct validity. A total of 110 questions were drafted with 5-point Likert scale answers. From the list, 31 were selected and subsequently tested on 158 participants. The results were analysed and validated using exploratory factor analysis on SPSS. Components were extracted and questions with low factor loading were removed. The internal consistency was then measured with Cronbach’s alpha. Results: Following analysis, 3 components were extracted and named as general stroke knowledge, hyperacute stroke care and advanced stroke management. Two items were deleted leaving 29 out of 31 questions for the final validated ASMaQ. Internal consistency showed high reliability with Cronbach’s alpha of 0.82. Our respondents scored a total cumulative mean of 113.62 marks or 66.6%. A sub analysis by occupation showed that medical assistants scored the lowest in the group with a score of 57% whilst specialists including neurologists scored the highest at 79.4%. Conclusion: The ASMaQ is a newly developed and validated questionnaire consisting of 29 questions testing the respondents’ acute stroke management knowledge.